2008
DOI: 10.1073/pnas.0712130105
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus evolution in vivo is constrained by host alternation

Abstract: The intrinsic plasticity of RNA viruses can facilitate host range changes that lead to epidemics. However, evolutionary processes promoting cross-species transfers are poorly defined, especially for arthropodborne viruses (arboviruses). In theory, cross species transfers by arboviruses may be constrained by their alternating infection of disparate hosts, where optimal replication in one host involves a fitness tradeoff for the other. Accordingly, freeing arboviruses from alternate replication via specializatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
197
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(213 citation statements)
references
References 38 publications
(53 reference statements)
11
197
3
2
Order By: Relevance
“…Passage history is another key concern for these viruses. Studies with VEEV have shown that removal of selective pressures associated with a two-host lifecycle results in accumulation of single nucleotide polymorphisms (SNPs), 46,47 and cell culture passages often result in adaptation for heparin sulfate binding, which can result in artificial attenuation. 48 Isolates with low numbers of passages and well-characterized passage histories would be a substantial benefit to the animal models.…”
Section: Path From Experimental Vaccines To Licensurementioning
confidence: 99%
“…Passage history is another key concern for these viruses. Studies with VEEV have shown that removal of selective pressures associated with a two-host lifecycle results in accumulation of single nucleotide polymorphisms (SNPs), 46,47 and cell culture passages often result in adaptation for heparin sulfate binding, which can result in artificial attenuation. 48 Isolates with low numbers of passages and well-characterized passage histories would be a substantial benefit to the animal models.…”
Section: Path From Experimental Vaccines To Licensurementioning
confidence: 99%
“…The maintenance of this cyclical transmission is vital to viral fitness, as prolonged serial passage within a single host results in attenuation in the alternate host (1)(2)(3)(4). Moreover, the ultimate outcome of alphaviral infection differs between vertebrate and invertebrate hosts, as infection of a vertebrate host results in acute cytolytic infection whereas infection of invertebrate hosts often results in persistent infection with minimal cell death (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Severe joint pain and rheumatoid arthritis (RA)-like symptoms, which begin at the onset of infection, can persist for months or even years after virus clearance and are the most notable markers of ChikV disease (65,66). One hypothesis for pathogenic symptoms during RA is the interaction of IgG with mast cells and cytokines (26,67). Furthermore, increased IgG titers have been shown to correlate with disease severity and persistence in ChikV infection (68).…”
Section: Discussionmentioning
confidence: 99%
“…The virus particles themselves are hybrid structures composed of membrane and glycosylation components derived from the host, but all protein and RNA is encoded by the virus (28). Viruses derived from insect or mammalian cells have been found to exhibit functional (7,26,29) and structural (30,31) differences that emphasize their hybrid nature. It is hypothesized that these agents have developed a consensus genome capable of expression in divergent biochemical environments by interacting specifically with each of these distinct hosts through sequence elements necessary for viral replication in one host but not necessarily the other (32)(33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation